Heroes and toilers : work as life in postwar North Korea, 1953-1961 - Kim, Cheehyung Harrison (Studies of the Weatherhead East Asian Institute, Columbia University., 2018)
Heroes and Toilers offers an unprecedented account of life and labor in postwar North Korea that looks at both governance and popular resistance. Cheehyung Harrison Kim traces the state's pursuit of progress through industrialism and examines how ordinary people challenged the state every step of the way.